Exploring innovative assessment and driving mechanisms for achieving land degradation neutrality in rocky desertification areas: A case study of Yunnan–Guangxi–Guizhou, China - Weihua Liao; Yifang Wei; Zhiyan Wei (Ecological Informatics)
Rocky desertification (RD), a manifestation of land degradation in humid and semi-humid zones, plays a pivotal role in pursuing the global goal of land degradation neutrality (LDN). However, the definition of desertification as outlined by the United Nations Convention to Combat Desertification is confined to arid and semi-arid territories, which may lead to neglect of RD emergence and rehabilitation within karst regions. To address this, the current study focused on the three most severely RD-affected provinces in China (Yunnan, Guangxi, and Guizhou) and developed a specialized LDN-RD assessment framework for RD areas to monitor the spatiotemporal dynamics of LDN. Furthermore, by employing a gradient boosting machine and Shapley Additive exPlanations values, this study investigated the influence of environmental factors and human endeavors on achievement of the LDN goal. Overall, the research findings indicated that: (1) from 2001 to 2020, Yunnan, Guangxi, and Guizhou provinces in China achieved the LDN target, with particularly notable performances in Guizhou and Guangxi; (2) environmental factors were the key determinants in achieving the LDN goal in RD areas, with nighttime light, low temperature, and water scarcity limiting achievement of LDN in degraded regions, and; (3) the introduction of an RD index enhanced the accuracy of identifying regional land-degradation phenomena. Therefore, we recommend global promotion of this new assessment framework in RD to support implementation of the LDN initiative. In summary, the full utilization and coordination of environmental factors in RD areas are highly important for accelerating achievement of the LDN goal.